DEVELOPMENT OF FIQIH THOHAROH FLIPBOOK BASED ON PROJECT BASED LEARNING ON RELIGIOUS COURSES IN FKIP UNIVERSITAS SRIWIJAYA - Fitriana Fitriana; Dian Erlina; Mukmin Mukmin (MUMTAZ : Jurnal Pendidikan Agama Islam, 2024)
This study aims to answer the needs in the learning process to be more effective through the development of teaching materials with the ADDIE model. The research method used is Research and Development (R&D) with qualitative and quantitative approaches. The ADDIE model involves five main stages: (1) Analysis, conducted through a needs analysis questionnaire and interviews; (2) Design, in the form of making flowcharts and storyboards; (3) Development, including validation by material, language, and teaching material design experts; (4) Implementation, with small and large scale trials through control and experimental classes; and (5) Evaluation, which focuses on revising and improving teaching materials. The feasibility test results show that the teaching materials developed have very good quality, with a percentage of design feasibility of 100% (Very valid), material feasibility of 95% (Very valid), and language feasibility of 97.5% (Very valid). In the effectiveness test of small-scale teaching materials, an average of 81.7% (Good) was obtained, while the large-scale trial obtained an average of 82.2% (Good). These results indicate that the teaching materials developed are effective and feasible to use in supporting the learning process.